Implementing a language awareness approach to grammar through topics : action research report (2006)
ABSTRACT: This small action research project evaluated the im pact of the implementation of a language awareness (LA) approach to grammar teachin g in a Grade 9 class in a public coed school in Bello (Antioquia, Colombia). Results indi cate that the fact of including a LA approach to grammar instruction does help the learn ers acquire a better understanding of how the structures work, and prepares them for future i ntegration of those structures in writing. However, the effectiveness of the approach can be i nfluenced by time constraints, and the fact of students having to adapt to a new way of teachin g grammar. Notwithstanding, the use of metalanguage in giving explicit grammar explanation s, the learners’ readiness to produce language using the targeted structures and the effe ctiveness of teaching in getting students to integrate those structures are worthy of further study.